Characteristics and risk factors of infections following CD28-based CD19 CAR-T cells. Issue 7 (7th June 2021) - Wittmann Dayagi, Talya; Sherman, Gilad; Bielorai, Bella; Adam, Etai; Besser, Michal J.; Shimoni, Avichai; Nagler, Arnon; Toren, Amos; Jacoby, Elad; Avigdor, Abraham
Abstract: CAR T-cells are approved for the treatment of relapsed and refractory leukemia and lymphoma. Here, we studied the infectious complications in 88 patients treated with CD28-based CD19 CAR T-cells. Overall, 36 infections were documented in 24 patients within the first month after CAR T-cell infusion: Six events of bacteremia, sixteen focal bacterial infections, and fourteen systemic or localized viral infections. Seven patients had nine infectious episodes beyond the first 30 days of follow-up, including three events of bacteremia, three focal bacterial, two viral and one fungal infection. The presence of neutropenia, neutropenic fever and lack of response to treatment were associated with a higher rate of infections. Children had less severe infections than adults. In a multivariate analysis lack of response to treatment was the only significant risk factor. Overall, the incidence of bacterial infections following CAR T-cells is modest especially in children and in patients responding to therapy.